Kebijakan Hukum Terhadap Fenomena Manipulasi Gelar Akademik di Indonesia - Faqih Zuhdi Rahman (Mavisha: Law and Society Journal, 2025)
This study analyzes the legal policies in Indonesia concerning the phenomenon of academic degree manipulation. The manipulation of academic degrees, such as the use of fake degrees or obtaining degrees through illegitimate means, has become a serious issue that erodes the integrity of education and professional ethics. The primary objective of this research is to identify and examine relevant regulations, evaluate their effectiveness in combating these illegal practices, and propose recommendations for policy improvements. The research employs a qualitative method with a normative juridical approach, focusing on the analysis of related laws, government regulations, and court decisions. The findings indicate that while Indonesia possesses an adequate legal framework, such as Law No. 12 of 2012 on Higher Education, its implementation still faces significant challenges. These challenges include a lack of strict supervision, legal loopholes, and low public awareness regarding the legal consequences of degree manipulation. Therefore, strategic measures are necessary, including strengthening the synergy among educational institutions, law enforcement agencies, and the public, as well as revising regulations to close existing loopholes. This research is expected to contribute significantly to the government's efforts to maintain the quality and credibility of the national education system.   Abstrak: Penelitian ini menganalisis kebijakan hukum yang berlaku di Indonesia terkait fenomena manipulasi gelar akademik. Manipulasi gelar, seperti penggunaan gelar palsu atau perolehan gelar melalui cara-cara yang tidak sah, telah menjadi isu serius yang merusak integritas pendidikan dan etika profesional. Tujuan utama studi ini adalah untuk mengidentifikasi dan mengkaji regulasi yang relevan, mengevaluasi efektivitasnya dalam menanggulangi praktik ilegal ini, serta mengusulkan rekomendasi untuk perbaikan kebijakan. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan yuridis normatif, berfokus pada analisis terhadap undang-undang, peraturan pemerintah, dan putusan pengadilan yang terkait. Hasil penelitian menunjukkan bahwa, meskipun Indonesia memiliki kerangka hukum yang memadai, seperti Undang-Undang Nomor 12 Tahun 2012 tentang Pendidikan Tinggi, implementasinya masih menghadapi tantangan. Tantangan tersebut meliputi kurangnya pengawasan yang ketat, celah hukum, serta rendahnya kesadaran publik tentang konsekuensi hukum dari manipulasi gelar. Oleh karena itu, diperlukan langkah-langkah strategis, seperti penguatan sinergi antara lembaga pendidikan, penegak hukum, dan masyarakat, serta revisi regulasi untuk menutup celah yang ada. Penelitian ini diharapkan dapat memberikan kontribusi signifikan bagi upaya pemerintah dalam menjaga kualitas dan kredibilitas sistem pendidikan nasional.